Public Sentiment About Waqf: Insights from Social Media Analysis with Talk Walker - Leny Agustin; Muhamad Subhi Apriantoro (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims to analyze public perceptions of waqf in Islamic finance through social media analysis, with the objective of understanding how societal interactions and demographic factors shape discourse and opinion formation regarding waqf.Methodology: The research adopts a qualitative-quantitative social media analytics approach grounded in social studies theory and prior literature. Data were collected on September 5, 2024, from multiple social media platforms using the Talkwalker Social Intelligence Platform. The analysis involved monitoring public opinion trends, conducting thematic analysis to identify recurring discourse themes, and applying Social Network Analysis (SNA) to examine interaction patterns related to waqf. Key influencing factors such as language, age, and gender were also examined. Results: The findings reveal significant trends in public reactions to waqf across social media platforms. Notable shifts in perceptions of waqf-related issues were identified, along with distinct patterns influenced by language use, age groups, and gender. The thematic analysis highlights dominant narratives and concerns surrounding waqf, providing a nuanced understanding of how social interactions shape public perceptions. Applications/Originality/Value: This study contributes original insights to the literature on Islamic finance and social studies by uncovering the complexity of societal responses to waqf in digital spaces. It demonstrates the value of integrating Social Network Analysis and social media intelligence tools, such as Talkwalker, to examine opinion dynamics and public discourse. The findings offer practical implications for policymakers, waqf institutions, and researchers in designing more effective communication and engagement strategies related to waqf.